Business process management : practical guidelines to successful implementations - Jeston, John; Nelis, Johan (Oxford : Butterworth-Heinemann, 2008)
"Business Process Management: Practical Guidelines to Successful Implementations" provides organizational leadership with an understanding of Business Process Management and its benefits to an organization. This is an easy-to-use, easy-to-read guide that provides a practical framework, complete with a set of tools and techniques, to successfully implement Business Process Management projects. In addition, it features vital organizational perspectives that not only provide an overall view of BPM and the move towards a process-centric organization, but also reveal how to embed BPM within an organization to ensure a continuous business process improvement culture.
Frequently asked questions -- How to demystify BPM -- What is Business Process Management(BPM)? -- Why is it important to improve business processes before automating them? -- When should you do BPM? -- What are the main drivers and triggers? -- Who should be involved in BPM? -- Why are organizational strategy and process architecture important in a BPM implementation? -- How do you sell BPM technology to the organization? -- What are the critical success factors in a BPM project? -- What are the critical implementation aspects of a BPM solution? -- Why do you need a structured approach to implementing BPM? -- The Framework -- Framework overview -- Guidelines of how to use the Framework -- Organization Strategy phase -- Process Architecture phase -- Launch Pad phase -- Understand phase -- Innovate phase -- People phase -- Develop phase -- Implement phase -- Realize Value phase -- Sustainable Performance phase -- Essentials Introduction -- Project Management -- People Change Management -- Leadership -- BPM and the organization -- BPM Maturity -- Embedding BPM within the organization
Includes bibliographical references and index.
1
Keywords: Introduction to Entrepreneurship and Small Business Management; Reengineering (Management); Organizational change; Business planning